2004
DOI: 10.1111/j.1365-3156.2004.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Local fever illness classifications: implications for home management of malaria strategies

Abstract: Summary Background  The Ugandan Ministry of Health has adopted the WHO Home Based Fever Management strategy (HBM) to improve access to antimalarial drugs for prompt (<24 h) presumptive treatment of all fevers in children under 5 years. Village volunteers will distribute pre‐packed antimalarials free of charge to caretakers of febrile children 2 months to 5 years (‘Homapaks’). Objective  To explore the local understanding and treatment practices for childhood fever illnesses and discuss implications for the HBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 23 publications
(39 reference statements)
9
44
2
Order By: Relevance
“…The perceived reduction in morbidity may lead to improvement in general health and well-being of the children and the communities as a whole. This also confirmed suggestions made in earlier studies 15,[19][20][21][22][23] that the best approach to managing malaria in endemic zones is to introduce an intervention at the community level, especially for vulnerable groups and hard to reach areas. 18 Benefits of improved health are enormous as children had the strength to go to school, play and stay-off their caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…The perceived reduction in morbidity may lead to improvement in general health and well-being of the children and the communities as a whole. This also confirmed suggestions made in earlier studies 15,[19][20][21][22][23] that the best approach to managing malaria in endemic zones is to introduce an intervention at the community level, especially for vulnerable groups and hard to reach areas. 18 Benefits of improved health are enormous as children had the strength to go to school, play and stay-off their caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…This feature is similar to that in many other countries who use CHWs for similar activities. [23][24][25] The ability to use this extensive network of health staff enabled quicker implementation of services and ultimately more extensive patient enrollment. We found that 79% of the patients identified during an evaluation were enrolled in the program and 79% of the patients enrolled were making yearly dispensary visits.…”
Section: Discussionmentioning
confidence: 99%
“…The local term for 'hot body' was used to ask about fever and, as biomedical terms to describe breathing rarely had exact equivalents in the local languages, 19 locally appropriate concepts of illness including symptoms of difficult and/or rapid breathing (DRB) were used for acute respiratory infection. This symptom combination and acronym will be in quotes throughout the paper to highlight that these are symptoms reported by mothers and do not necessarily correspond with clinical symptoms.…”
Section: Data Collection and Analysismentioning
confidence: 99%